PENGEMBANGAN INSTRUMEN SIKAP SPIRITUAL PADA SISWA SEKOLAH DASAR - Muhammad Ichsan (Jurnal Evaluasi Pendidikan, 2017)
The purpose of this research is to develop spiritual behavior instrument for elementary students. This research used SEM method with second order confirmatory factor analysis with 300 students as the respondents. This study is held in two stageswith 150 respondents in each of them to validate empirical construct and the fitness of the model in overall.The result showed that there were 3 dimensions and 12 indicators with loading factor of Î» â‰¥ 0.30, t-calculation â‰¥ t-table, and the model meets almost all of goodness of fit index criteria as the requirements to conclude that the model is fit with CR = 0.846 > 0.7 and VE = 0.599 > 0.5. Therefore, the instrument of spiritual attitude for elementary students is deemed valid and reliable.